(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the positive predictive value of CA125 for ovarian masses taking histopathology as gold standard. Methods: 65 patients of all ages with adnexal masses were included in this study. This study was carried out in the department of pathology Fatima Jinnah medical college/ Sir Ganga Ram Hospital Lahore in six months period. Results: Out of 65 patients, 43 patients presents with raised CA 125 levels. Out of these 43 patients 32 have serum CA 125 level between 35U/ml-200U/ml, 14 patients were confirmed to have malignant ovarian tumour and 18 have benign tumour. The positive predictive value is 44%. 11 patients have CA 125 level more than 200U/ml, 10 patients have malignant ovarian tumour and 1 patient was confirmed to have benign ovarian tumour on histopathology. The positive predictive value is 90%. So it is concluded that CA 125 is an important tumour marker to determine the nature of ovarian mass preoperatively as very high levels (more than 200 u/ml) are mostly found in ovarian carcinomas and it helps in further management plan.